How do opinion polls affect voters? The effect of opinion polls on the Danes’ voting behavior and sympathy for parties - Dahlgaard, Jens Olav; Hansen, Jonas Hedegaard; Hansen, Kasper Møller; Larsen, Martin Vinæs (Politica, 2015)
Information like opinion polls can influence public opinion. We present two hypotheses to understand how polls affect voters: First, the bandwagon effect claims that voters “float along”: A party experiencing increased support receives more support and vice versa. Second, the underdog effect claims that a party experiencing declining support receives sympathy votes. Through a survey experiment we find evidence of the bandwagon effect, and the effect is strongest in the positive direction, that is, when a party experiences increased support more will follow. The negative bandwagon effect also finds support, but there is no support for the underdog effect. The effects are in the same direction regardless of the size of the party. We discuss whether publication of opinion polls should be banned.